Failure mode and effect analysis of an iron ore recovery machine - Costa, Maurélio Ferreira; Teixeira, Felipe Ribeiro; Brito, Matheus da Cunha; Martins, Harley dos Santos; Cardoso, Louíse de Castro Lobo (Brazilian Journal of Production Engineering, 2026)
The objective of this work is to increase the physical availability of an iron ore recovery machine. To this end, the Failure Mode and Effect Analysis methodology was used, which is widely used in the literature and often referred to by the acronym FMEA (Failure Mode and Effect Analysis). After identifying the potential causes of failure, corrective actions were proposed and carried out by the maintenance team. In the end, an improvement in the physical availability indicator was observed.
Keywords: Mining; FMEA; Physical availability